2011
DOI: 10.1186/1475-2840-10-89
|View full text |Cite
|
Sign up to set email alerts
|

An association between TRP64ARG polymorphism of the B3 adrenoreceptor gene and some metabolic disturbances

Abstract: BackgroundsB3 adrenoreceptors (ADRB3) are abundant in adipose tissue and play the role in its metabolism and lipolysis. Some variants of the ADRB3 gene may predispose subjects for the development obesity and metabolic abnormalities in the setting of modern sedentary lifestyle. ADRB3 gene polymorphism association with metabolic disturbances has never been studied before in the ethnic Kyrgyz population.AimTo study an association between Trp64Arg polymorphism of the ADRB3 and metabolic syndrome (MS) components in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 35 publications
3
37
0
Order By: Relevance
“…19 Trp64Arg polymorphism has been reported to be associated with obesity, central obesity, weight gain, insulin resistance, type 2 diabetes mellitus, hypereruricemia 20 and metabolic syndrome. 21 Cohort studies have shown rs4994 to be a genetic risk factor for cardiovascular disease in hypertensive patients. 22 However, the effect of rs4994 remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…19 Trp64Arg polymorphism has been reported to be associated with obesity, central obesity, weight gain, insulin resistance, type 2 diabetes mellitus, hypereruricemia 20 and metabolic syndrome. 21 Cohort studies have shown rs4994 to be a genetic risk factor for cardiovascular disease in hypertensive patients. 22 However, the effect of rs4994 remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The other limitation of this study was that the number of subjects in the genotype subgroups of the Trp64Arg polymorphism might not be sufficient to completely identify the effect of gene–intervention interaction on weight loss or other parameters, particularly that we did not find the Arg64Arg polymorphism in our study population. However, its frequency has often been reported to be low in other populations (Mirrakhimov et al ., ; Tsunekawa et al ., ). Moreover, because there was no other intervention such as weight‐lowering diet across the study, it might be better to design an intervention with higher dose of ginger powder (i.e., 3 g) to reach more efficacy of intervention, just as a suggestion for future researches, because it is a safe herbal medicine according to existing data and also the FDA's report on its safety (Li et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The present study also showed a gene–treatment interaction on HDL‐C levels. The Arg64 allele was cross‐sectionally associated with a decreased HDL‐C level in obese Japanese people and a Kyrgyz population, although a few studies described conflicting data – no association with HDL‐C or association with higher HDL‐C levels was found in Caucasian‐Brazilian patients with type 2 diabetes. An increase of HDL‐C levels is important for preventing the development of diabetes mellitus and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%